Orientalismo impresso: a revolução iraniana sob o prisma dos jornais Clarin e Folha de São Paulo (1979-1981) - Zanoni, David Anderson (2020)
This doctoral thesis aims to analyze and understand the process of Iranian government change from 1979 onwards through the periodical press. For this purpose, the newspapers Clarin, from Argentina, and the Brazilian daily, Folha de S. Paulo, were chosen as research objects and sources. The process of overthrowing the autocratically ruled monarchy by Mohammad Reza Pahlavi, the shah of Iran, has collapsed after 37 years of holding on to power. His regime was replaced by a republic, captained by Ayatollah Ruhollah Musavi Khomeini. The process of the fall of the monarchy and the rise of the Islamic Republic of Iran was reported by media outlets around the world. In this study, we are interested in analyzing the content of the aforementioned periodicals to analyze in what ways these media outlets produced news that reported Iran and its political process to readers. We aim to observe if and how the production of meanings or representations of Iran, its people, culture and religiosity occurred from the developments of the Iranian revolution. The history of contemporary Iran, especially from the Pahlavi dynasty (1925-1979), when the country was ruled first by his father Reza Khan Pahlavi, and then by his son, Mohammad Reza Pahlavi, until the establishment of the Islamic Republic, are elements presented for understanding the context in which this study is inserted. The geopolitical relations established between the West, first by England and, after World War II, by the United States with Iran are also elements of analysis, as they contextualize the West and Islamic East relations. Finally, all the issues presented here are inserted in the field of debate of Orientalism, that is, a concept coined by Edward Said that deals with the construction of the Orient by the West through a detailed intellectual framework that legitimizes Western domination over territories of the Islamic Orient. Therefore, it is intended to understand History through the press with a theoretical framework that brings together the History of the present time and Political History, against the backdrop of the Iranian Revolution of 1979 under the prism of the newspapers that were selected for this study.